Microstructures and properties of microporous magnesia aggregates from Mg(OH)2 and magnesite - Jinling Shi; Jianhua Nie; Wen Yan; Zheng Han; Xiao Wang; Yuanbing Li; Jinwen Song (Journal of Asian Ceramic Societies, 2025)
Microporous MgO refractory aggregates were prepared with Mg(OH)2 and magnesite by the in-situ decomposition method, and the influence of magnesite content on the microstructures and properties of the aggregates was investigated. The results indicated that a large amount of nanopores generated in the aggregates without magnesite due to Mg(OH)2 decomposition, but few neck connections among MgO particles. Some impurities in appropriate magnesite leading to liquid-phase sintering promoted the formation of neck connections and thus improved the strength and thermal shock resistance. However, excessive introduction of magnesite resulted in the enlargement of the pores and the increase of porosity and then deteriorated the properties of the aggregates. The sample with 15 wt.% magnesite content exhibited the best comprehensive properties, with a bulk density of 2.82 g/cm3, a median pore size of 2.45 um, a compressive strength of 68.2 MPa, a high thermal shock resistance and a relatively low thermal conductivity of 5.76 W/(m K) at 800 ℃.